Design, mathematical modelling and experimental investigation of vacuum insulated semi-transparent thin-film photovoltaic (PV) glazing. (September 2020) - Jarimi, Hasila; Lv, Qinghua; Ramadan, Omar; Zhang, Shihao; Riffat, Saffa
Abstract: This paper aims to investigate a novel design of vacuum insulated semi-transparent thin-film photovoltaic (PV) glazing called 'PV VG-2L', focusing on its thermal performance. The PV VG-2L consists of two parallel glass panes; a semi-transparent thin-film PV glass and a 4 mm hard low-E coated glass, separated by a 0.3 mm vacuum gap. Unlike the conventional vacuum glazing that uses stainless steel, ceramic or alumina as the support pillars, strong and low thermally conductive aerogel material was employed to prevent the glass panes from collapsing under atmospheric pressure. To investigate its performance, a mathematical model for PV VG-2L was developed and numerically solved in MATLAB. The developed model was then validated against indoors and outdoors lab-scale experiments. To conduct the experiments, two PV VG-2L prototypes were manufactured using an innovative low-temperature high-level vacuum method. Using the validated mathematical model, at its optimum design, the performance of the PV VG-2L was numerically simulated, yielding an average U-value as low as 0.60 W/m 2 K. The promising U-value implies that the PV VG-2L investigated in this research has a wide range of potential applications depending on the energy needs and application. Highlights: A novel semi-transparent thin-film PV vacuum glazing (PV VG-2L) with low U-value. Strong and low-thermally conductive aerogel material as the support pillars. An innovative manufacturing method using two types of low-temperature solder. Energy balance equations developed and numerically solved in MATLAB. The promising U-value implies its potential in building integrated application.